1943
DOI: 10.1002/jctb.5000620704
|View full text |Cite
|
Sign up to set email alerts
|

Dried meat. II. the growth of moulds on dried meat

Abstract: July, 1114s simplicity in operntion nnd giving optimal qunlity in both the raw and precooked product. At this teniperature the time required to dry raw meat was considerably longer thnn for precooked meat, mainly on nccount of very slow drying in the later stnges. A great improvement ivns brought nbout by remilicing nfter nbout 75-85y0 of the original moisture hod been removed (Fig. 2). Howdver. after a fnir trial i t wns renlised that the qunlity of dried raw nient was, at its best, not equal to that of dried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1949
1949
2000
2000

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The factors influencing the growth of moulds on various stored products have been described by several authors. These include observations on book-binding materials by Groom & Panisset (1933), on textiles by Galloway (1935), on leather by Colin-Russ (1940), on dried meat by Macara (1943), and on feeding stuffs by Snow, Crichton & Wright (1944). It has been shown that the development of moulds on various materials is conditioned by the relative humidity of the storage atmosphere rather than by the moisture content of the materials themselves.…”
Section: Introductionmentioning
confidence: 99%
“…The factors influencing the growth of moulds on various stored products have been described by several authors. These include observations on book-binding materials by Groom & Panisset (1933), on textiles by Galloway (1935), on leather by Colin-Russ (1940), on dried meat by Macara (1943), and on feeding stuffs by Snow, Crichton & Wright (1944). It has been shown that the development of moulds on various materials is conditioned by the relative humidity of the storage atmosphere rather than by the moisture content of the materials themselves.…”
Section: Introductionmentioning
confidence: 99%
“…The possible non-oxidative deteriorative reactions in freeze-dried beef during storage are rather limited. The moisture content is so low that mold growth may be eliminated from consideration (11). Also, enzymatic reactions would be non-existent or a t least negligible a t this moisture level.…”
Section: Discussionmentioning
confidence: 99%